Cryptocurrency in The Perspective of Maqasid Al-Shariah - Wartoyo Wartoyo; Alvien Septian Haerisma (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2022)
This study explains the Islamic economic perspective on cryptocurrency, in this case, in the light of maqashid shariah. This research was a literature study and qualitative in nature. The data analysis applied a descriptive-analytical technique with a normative juridical approach to Islamic law. The results of this study conclude that cryptocurrency has a much greater element of mafsadah than maslahah. It is an investment commodity rather than a currency with a very high level of risk and volatility that reflects the mafsadah. This is the attraction of a new investment model because it only follows the trend of global market developments that are far from the function and benefits of currency in the perspective of Islamic economics.